Gradient pre‐emphasis to counteract first‐order concomitant fields on asymmetric MRI gradient systems. Issue 6 (4th July 2016) - Tao, Shengzhen; Weavers, Paul T.; Trzasko, Joshua D.; Shu, Yunhong; Huston, John; Lee, Seung‐Kyun; Frigo, Louis M.; Bernstein, Matt A.
Abstract : Purpose: To develop a gradient pre‐emphasis scheme that prospectively counteracts the effects of the first‐order concomitant fields for any arbitrary gradient waveform played on asymmetric gradient systems, and to demonstrate the effectiveness of this approach using a real‐time implementation on a compact gradient system. Methods: After reviewing the first‐order concomitant fields that are present on asymmetric gradients, we developed a generalized gradient pre‐emphasis model assuming arbitrary gradient waveforms to counteract their effects. A numerically straightforward, easily implemented approximate solution to this pre‐emphasis problem was derived that was compatible with the current hardware infrastructure of conventional MRI scanners for eddy current compensation. The proposed method was implemented on the gradient driver subsystem, and its real‐time use was tested using a series of phantom and in vivo data acquired from two‐dimensional Cartesian phase‐difference, echo‐planar imaging, and spiral acquisitions. Results: The phantom and in vivo results demonstrated that unless accounted for, first‐order concomitant fields introduce considerable phase estimation error into the measured data and result in images with spatially dependent blurring/distortion. The resulting artifacts were effectively prevented using the proposed gradient pre‐emphasis. Conclusion: We have developed an efficient and effective gradient pre‐emphasis framework to counteract the effects of first‐order concomitant fields of asymmetric gradient systems.Magn Reson Med 77:2250–2262, 2017. © 2016 International Society for Magnetic Resonance in Medicine